The influence of heat and cold stress on gluten protein and starch in wheat - Oskar, Elago (University of the Free State, 2007)
The ability of wheat flour to be processed into bread and other products is largely determined by the gluten proteins, which confer unique visco-elastic properties to dough. These proteins are influenced by genetic make up and the environment in which the plants are grown. The objective of this study was to gain a better understanding of the influence of extreme temperatures on the gluten proteins, quality characteristics, starch and starch components. Two bread wheat cultivars, a soft biscuit wheat and a durum wheat were grown two plants to a pot, with 12 pots for each replication, with three replications in a greenhouse for two consecutive years. Cold and heat treatments were applied during grain filling. Size exclusion and reverse phase HPLC were used to measure the different protein fractions. Starch, amylose, amylopectin and various quality characteristics were measured on all entries after harvest in both years. The results from this study showed that in both years the softest cultivar, Snack showed the largest reaction to low temperature stress specifically, where the monomeric proteins were significantly increased, and the polymeric proteins were significantly decreased. In the second year SST86 showed the same trend as Snack under cold stress conditions. Oranje, the durum wheat cultivar, reacted to both heat and cold stress in the second year, where the small polymeric proteins (SDS soluble) were significantly reduced, and the small monomeric proteins were increased with stress, and the SDS insoluble large monomeric proteins were increased only under heat stress. The protein fractions of the tetraploid Oranje were very different from that of the other three hexaploid cultivars. The soft wheat Snack had significantly lower large polymeric protein, and higher large monomeric protein fractions (SDS insoluble) than the bread wheat cultivars for both years. Summed over cultivars, per treatment for the two years, all the fractions, except for the small polymeric and small monomeric proteins (SDS insoluble) were affected by the cold treatment. The monomeric proteins were consistently increased, and the polymeric proteins decreased. Only the SDS soluble large polymeric proteins were significantly affected by the heat treatment, where it was significantly decreased. Both kernel weight and diameter were significantly decreased at both stress treatments for the two bread wheat cultivars, indicating that their kernel characteristics were sensitive to extreme temperatures. Across the two seasons, the starch content in Kariega was significantly reduced by both heat and cold temperatures, as is also reflected in the reduction of kernel weight and diameter. Amylose content and the amylose:amylopectin ratio increased under heat and cold treatment. There were highly significant positive and negative correlations between certain RP-HPLC peaks and quality characteristics for all three the temperature treatments in both years. The number of significant correlations was reduced under the two stress conditions, but there is a possibility to use certain peaks for quality selection. The profiles must, however, be standardised so that peaks can be scored and compared on any gel according to their elution times. Stepwise regression also emphasized the importance of some of the RP-HPLC peaks in explaining variation in flour protein content and SDS sedimentation for all three temperature treatments.

Die vermoë van koring meel om verwerk te word na brood en ander produkte, word grootliks bepaal deur die gluten proteïene, wat visko-elastiese eienskappe aan deeg gee. Hierdie proteïene word geneties bepaal, maar word ook deur die omgewing beïnvloed waarin die plante groei. Die doel van hierdie studie was om ‘n beter begrip te kry van die invloed van uiterste temperature op die gluten proteïene, kwaliteitseienskappe, stysel en stysel komponente. Twee broodkoring kultivars, ‘n sagte koekiekoring en ‘n durum koring is geplant, twee plante per pot, met 12 potte per herhaling, en drie herhalings, in die glashuis, in twee opeenvolgende jare. Koue en hitte behandeling is toegedien tydens die graanvul periode. SE- en RP-HPLC is gebruik om die verskillende proteïenfraksies te skei. Stysel, amilose en amilopektien, en verskeie kwaliteits eienskappe is gemeet na oes in beide jare. Die resultate van hierdie studie het getoon dat die sagte koring kultivar, Snack, die grootste reaksie getoon het op lae temperatuur stremming spesifiek, waar die monomeriese proteïene betekenisvol toegeneem en die polimeriese proteïene betekenisvol afgeneem het. In die tweede jaar het SST86 dieselfde tendens getoon as Snack onder koue temperatuur stremming. Oranje, die durum koring kultivar, het gereageer op beide hitte en koue stremming in die tweede jaar, waar SDS oplosbare klein polimeriese proteïene afgeneem het en klein monomeriese proteïene toegneem het. Die SDS onoplosbare groot monomeriese proteïene het slegs onder hitte stremming toegeneem. Die proteïen fraksies van die tetraploïede Oranje was baie verskillend van die van die drie heksaploïede koring kultivars. Die sagte koring Snack het betekenisvol minder groot polimeriese proteïene en meer monomeriese proteïene (SDS onoplosbaar) gehad as die broodkorings in beide jare. Waar data saamgevoeg is oor cultivars oor jare vir die verskillende behandelings, is al die proteïen fraksies behalwe die klein polimeriese en klein monomeriese (SDS onoplosbaar) proteïene geaffekteer deur die koue behandeling. Die monomeriese proteïene het konstant toegeneem, en die polimeriese proteïene het konstant afgeneem. Net die SDS oplosbare groot polimeriese proteïene is deur die hitte behandeling beïnvloed, waar dit betekenisvol afgeneem het. Beide korrel massa en deursnee is betekenisvol verminder deur beide stremmings behandelings in die twee broodkoring cultivars, wat aandui dat die twee culivars sensitief is vir uiterste temperature. Oor beide die jare, het die styselinhoud van Kariega betekenisvol afgeneem onder beide die stremmmings behandelings, wat ook gereflekteer is in die afname van die korrelmassa en deursnee. Amilose inhoud en amilose:amilopektien verhouding het toegneem onder beide stremming behandelings. Daar was hoogs betekenisvolle positiewe en negatiewe korrelasies tussen sekere RP-HPLC pieke en kwaliteits eienskappe vir al drie die temperatuur behandelings in beide jare. Die aantal betekenisvolle korrelasies was minder onder stremmings toestande, maar daar bestaan moontlikhede om sekere pieke te gebruik om kwaliteits seleksie te doen. Die proteïenprofiele sal egter gestandardiseer moet word sodat sodat pieke van verskillende profiele met mekaar vergelyk kan word op grond van tye waar pieke vorm. Stapsgewyse regressie het ook die belangrikheid van sommige RP-HPLC pieke uitgewys in die verduideliking van variasie in meel proteïen inhoud en SDS sedimentasie vir al drie temperaturuur behandelings.
Dissertation (M.Sc.Agric. (Plant Sciences))--University of the Free State, 2007
Keywords: Wheat -- South Africa -- Quality; Gluten; Proteins; Wheat -- Effect of temperature on